Using design of experiments (DoE) to optimize performance and stability of biomimetic cell membrane-coated nanostructures for cancer therapy - Ferreira, Natália Noronha; Miranda, Renata Rank; Moreno, Natália Sanchez; Pincela Lins, Paula Maria; Leite, Celisnolia Morais; Leite, Ana Elisa Tognoli; Machado, Thales Rafael; Cataldi, Thaís Regiani; Labate, Carlos Alberto; Reis, Rui Manuel; Zucolotto, Valtencir (Frontiers in Bioengineering and Biotechnology, 2023)
Biomimetic nanosystems based on cell membrane-covered nanoparticles have allowed the development of homologous nanostructures to bestow nanoparticles with enhanced biointerfacing capabilities. However, such structures still represent a great challenge for the scientific community, especially regarding stability. The present study aimed to develop and optimize cell-derived membrane-coated nanostructures by applying a design of experiments to improve the therapeutic index by homotypic targeting in cancer cells. Important physicochemical features of the extracted cell membrane from tumoral cells were assessed by mass spectrometry-based proteomics. PLGA-based nanoparticles encapsulating temozolomide were successfully developed. The coating technology applying the isolated U251 cell membrane was optimized using a fractional two-level three-factor factorial design. All the formulation runs were systematically characterized regarding their diameter, polydispersity index, and zeta potential. Experimental conditions generated by DoE were also subjected to morphological studies using transmission electron microscopy. Its short-time stability was also assessed. MicroRaman and Fourier-Transform Infrared spectroscopies and Confocal microscopy were used as characterization techniques for evaluating the NP-MB nanostructures. Internalization studies were carried out to evaluate the homotypic targeting ability. The results have shown that nearly 80% of plasma membrane proteins were retained in the cell membrane vesicles after the isolation process, including key proteins to the homotypic binding. DoE analysis considering acquired TEM images reveals that condition run five should be the best-optimized procedure to produce the biomimetic nanostructure (NP-MB). Storage stability for at least two weeks of the biomimetic system is expected once the original characteristics of diameter, PDI, and ZP, were maintained. Raman, FTIR, and confocal characterization results have shown the successful encapsulation of TMZ drug and provided evidence of the effective coating applying the MB. Cell internalization studies corroborate the proteomic data indicating that the optimized NP-MB achieved specific targeting of homotypic tumor cells. The structure should retain the complex biological functions of U251 natural cell membranes while exhibiting physicochemical properties suitable for effective homotypic recognition. Together, these findings provide coverage and a deeper understanding regarding the dynamics around extracted cell membrane and polymeric nanostructures interactions and an in-depth insight into the cell membrane coating technology and the development of optimized biomimetic nanostructured systems.